2017
DOI: 10.4315/0362-028x.jfp-16-505
|View full text |Cite
|
Sign up to set email alerts
|

Study of Biofilm Formation Ability of Foodborne Arcobacter butzleri under Different Conditions

Abstract: The transmission of Arcobacter butzleri , an emerging food- and waterborne pathogen, is possibly favored by its ability to adhere to abiotic surfaces. In this study, we assessed the biofilm formation ability of 42 A. butzleri isolates recovered from different food products. Overall, nine isolates (21.4%) were able to adhere to polystyrene. Among them, a chicken-derived isolate was classified as strongly adherent. Based on the chi-square test, no relation was found between the adhesive abilities of the isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 32 publications
4
32
3
1
Order By: Relevance
“…A. butzleri is the most prevalent species of this genus in meat products (chicken, pork, beef, lamb), milk, cheese, and shellfish (Figueras et al, 2011a,b; Patyal et al, 2011; Shah et al, 2012; Hausdorf et al, 2013; Lee and Choi, 2013; Rahimi, 2014; Ramees et al, 2014; Lehmann et al, 2015; Ferreira et al, 2016). The presence and persistence in these niches, also endowed by the ability to form biofilms (Ferreira et al, 2013; Girbau et al, 2017), favor its spread and transmission to shellfish and farm animal, and increase the risk associated with food consumption. Although few fragmented studies have been carried out to assess the occurrence of this species in shellfish, A. butzleri has been found as the most common species in bivalve molluscs (mussels, clams, oysters, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…A. butzleri is the most prevalent species of this genus in meat products (chicken, pork, beef, lamb), milk, cheese, and shellfish (Figueras et al, 2011a,b; Patyal et al, 2011; Shah et al, 2012; Hausdorf et al, 2013; Lee and Choi, 2013; Rahimi, 2014; Ramees et al, 2014; Lehmann et al, 2015; Ferreira et al, 2016). The presence and persistence in these niches, also endowed by the ability to form biofilms (Ferreira et al, 2013; Girbau et al, 2017), favor its spread and transmission to shellfish and farm animal, and increase the risk associated with food consumption. Although few fragmented studies have been carried out to assess the occurrence of this species in shellfish, A. butzleri has been found as the most common species in bivalve molluscs (mussels, clams, oysters, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The ability to form biofilm can vary greatly among strains of the same species depending on extrinsic factors such as nutrient availability, environmental conditions and surface properties (Girbau et al , 2017 ). In this respect, it is important to point out that even weakly adherent isolates can produce biofilm and therefore be difficult to eliminate from the food chain (Srey et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of bacteria to adhere to and grow on abiotic surfaces is a critical issue for industries with suitable environments for biofilm formation (Girbau et al 2017 ) including food industries, where organic and inorganic residues easily accumulate. Product contact with these biofilms can lead to health problems if contaminated by pathogenic bacteria (Mafu et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average and the statistical difference among them are shown in Table 3. The strains evaluated exhibited a significant difference, as observed by Ferreira et al (2013); Girbau et al (2017) and Ferreira et al (2018), that found significant difference among the Arcobacter strains studied. The LMG 10828 T strain, was also evaluated by Ferreira et al (2013) and, as in the present investigation, showed high ability to form biofilm.…”
Section: Biofilms Formation On Contact Surfacesmentioning
confidence: 80%